Nannies, Migration and Early Childhood Education and Care : an International Comparison of in-Home Childcare Policy and Practice - Adamson, Elizabeth (Policy Press, 2017)
This book presents new empirical research about in-home child care in Australia, the United Kingdom and Canada, three countries where governments are pursuing new ways to support the recruitment of in-home childcare workers through funding, regulation and migration.